HAK ASASI MANUSIA SEBAGAI JAMINAN KONSTITUSI DI INDONESIA - ST. Nirwansyah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2019)
Discussions on Human Rights will never end as long as there is still human life on this earth. Moreover, the current situation of the international community is colored by opposition and violence, ranging from ethnic conflicts, national boundaries, wars to terrorism. Presumably it has indeed become a human nature that in his life it is always colored with conflicts, both ideological, political, economic, social and cultural conflicts. In Indonesia the strengthening of human rights as a guarantee of the constitution is regulated in Articles 28 A to J in the Indonesian Constitution in 1945. On this matter human rights are demands that can be enforced legally and attached to each individual or group of individuals to guarantee respect towards the dignity of his humanity.